Skip to content
Related Articles

Related Articles

Improve Article

Class 12 RD Sharma Solutions – Chapter 20 Definite Integrals – Exercise 20.1 | Set 1

  • Last Updated : 02 Jun, 2021
Geek Week

Evaluate the following definite integrals:

Question 1. \int_{4}^{9} \frac{1}{\sqrt{x}}dx

Solution:

We have,

I = \int_{4}^{9} \frac{1}{\sqrt{x}}dx

I = \left[\frac{x^{\frac{-1}{2}+1}}{\frac{-1}{2}+1}\right]^9_4

I = \left[\frac{x^{\frac{1}{2}}}{\frac{1}{2}}\right]^9_4



I = \left[2\sqrt{x}\right]^9_4

I = 2[√9 – √4 ] 

I = 2 (3 − 2)

I = 2 (1)

I = 2

Therefore, the value of \int_{4}^{9} \frac{1}{\sqrt{x}}dx       is 2.

Question 2. \int_{-2}^{3} \frac{1}{x+7}dx

Solution:

We have,



I = \int_{-2}^{3} \frac{1}{x+7}dx

I = \left[log(x+7)\right]^3_{-2}

I = log (3 + 7) − log (−2 + 7)

I = log 10 − log 5

I = log\frac{10}{5}

I = log 2

Therefore, the value of \int_{-2}^{3} \frac{1}{x+7}dx       is log 2.

Question 3. \int_{0}^{\frac{1}{2}} \frac{1}{\sqrt{1-x^2}}dx

Solution:

We have,

I = \int_{0}^{\frac{1}{2}} \frac{1}{\sqrt{1-x^2}}dx



Let x = sin t, so we have, 

=> dx = cos t dt

Now, the lower limit is,

=> x = 0 

=> sin t = 0

=> t = 0

Also, the upper limit is,

=> x = 1/2

=> sin t = 1/2

=> t = π/6

So, the equation becomes,

I = \int_{0}^{\frac{\pi}{6}} \frac{1}{\sqrt{1-sin^2t}}costdt

I = \int_{0}^{\frac{\pi}{6}} \frac{1}{\sqrt{cos^2t}}costdt

I = \int_{0}^{\frac{\pi}{6}} (\frac{1}{cost})costdt

I = \int_{0}^{\frac{\pi}{6}} 1dt

I = \left[t\right]_0^{\frac{\pi}{6}}

I =  π/6 – 0

I = π/6

Therefore, the value of \int_{0}^{\frac{1}{2}} \frac{1}{\sqrt{1-x^2}}dx       is π/6.

Question 4. \int_{0}^{1} \frac{1}{1+x^2}dx

Solution:



We have,

I = \int_{0}^{1} \frac{1}{1+x^2}dx

I = \left[tan^{-1}x\right]_0^1

I = tan^{-1}1-tan^{-1}0

I = \frac{\pi}{4}-0

I = π/4

Therefore, the value of \int_{0}^{1} \frac{1}{1+x^2}dx       is π/4.

Question 5. \int_{2}^{3} \frac{x}{x^2+1}dx

Solution:

We have,

I = \int_{2}^{3} \frac{x}{x^2+1}dx



Let x2 + 1 = t, so we have,

=> 2x dx = dt

=> x dx = dt/2

Now, the lower limit is, x = 2

=> t = x2 + 1

=> t = (2)2 + 1

=> t = 4 + 1

=> t = 5

Also, the upper limit is, x = 3

=> t = x2 + 1

=> t = (3)2 + 1

=> t = 9 + 1

=> t = 10

So, the equation becomes,

I = \int_{5}^{10} \frac{1}{2t}dt

I = \frac{1}{2}\int_{5}^{10} \frac{1}{t}dt

I = \frac{1}{2}\left[logt\right]^{10}_5

I = 1/2[log10 – log5] 

I = 1/2[log10/5]

I = 1/2[log2]

I = log√2

Therefore, the value of \int_{2}^{3} \frac{x}{x^2+1}dx       is log√2.

Question 6. \int_{0}^{\infty} \frac{1}{a^2+b^2x^2}dx

Solution:

We have,

I = \int_{0}^{\infty} \frac{1}{a^2+b^2x^2}dx

I = \int_{0}^{\infty} \frac{1}{b^2}\left(\frac{1}{\frac{a^2}{b^2}+x^2}\right)dx

I = \frac{1}{b^2}\int_{0}^{\infty}\frac{1}{\frac{a^2}{b^2}+x^2}dx

I = \frac{1}{b^2}\left[\frac{b}{a}tan^{-1}\frac{bx}{a}\right]^{\infty}_{0}

I = \frac{1}{ab}\left[tan^{-1}\frac{bx}{a}\right]^{\infty}_{0}

I = 1/ab[tan-1∞ – tan-10] 



I = 1/ab[π/2 – 0]  

I = 1/ab[π/2]  

I = π/2ab   

Therefore, the value of \int_{0}^{\infty} \frac{1}{a^2+b^2x^2}dx       is π/2ab.

Question 7. \int_{-1}^{1} \frac{1}{1+x^2}dx

Solution:

We have,

I = \int_{-1}^{1} \frac{1}{1+x^2}dx

I = \left[tan^{-1}x\right]_{-1}^{1}

I = [tan-11 – tan-1(-1)]  

I = [π/4 – (-π/4)]   

I = [π/4 + π/4]  

I = 2π/4 

I = π/2  

Therefore, the value of \int_{-1}^{1} \frac{1}{1+x^2}dx       is π/2.

Question 8. \int_{0}^{\infty} e^{-x}dx

Solution:

We have,

I = \int_{0}^{\infty} e^{-x}dx

I = \left[-e^{-x}\right]^{\infty}_{0}

I = -e – (-e0) 

I = − 0 + 1



I = 1

Therefore, the value of \int_{0}^{\infty} e^{-x}dx       is 1.

Question 9. \int_{0}^{1} \frac{x}{x+1}dx

Solution:

We have,

I = \int_{0}^{1} \frac{x}{x+1}dx

I = \int_{0}^{1} \frac{(x+1)-1}{x+1}dx

I = \int_{0}^{1} \frac{x+1}{x+1}dx-\int_{0}^{1}\frac{1}{x+1}dx

I = \int_{0}^{1} 1dx-\int_{0}^{1}\frac{1}{x+1}dx

I = \left[x\right]^1_0-\left[log(x+1)\right]^1_0

I = [1 − 0] − [log(1 + 1) − log(0 + 1)]



I = 1 − [log2 − log1]

I = 1 – log2/1 

I = 1 − log 2

I = log e − log 2

I = loge/2 

Therefore, the value of \int_{0}^{1} \frac{x}{x+1}dx        is loge/2.

Question 10. \int_{0}^{\frac{\pi}{2}} (sinx+cosx)dx

Solution:

We have,

I = \int_{0}^{\frac{\pi}{2}} (sinx+cosx)dx

I = \int_{0}^{\frac{\pi}{2}} (sinx)dx+\int_{0}^{\frac{\pi}{2}}(cosx)dx

I = \left[-cosx\right]_{0}^{\frac{\pi}{2}}+\left[sinx\right]_{0}^{\frac{\pi}{2}}

I = [-cosπ/2 + cos0] + [sinπ/2 – sin0] 

I = [−0 + 1] + 1

I = 1 + 1

I = 2

Therefore, the value of \int_{0}^{\frac{\pi}{2}} (sinx+cosx)dx      is 2.

Question 11. \int_{\frac{\pi}{4}}^{\frac{\pi}{2}} cotxdx

Solution:

We have,

I = \int_{\frac{\pi}{4}}^{\frac{\pi}{2}} cotxdx

I = \left[log(sinx)\right]_{\frac{\pi}{4}}^{\frac{\pi}{2}}



I = log(sinπ/2) – log(sinπ/4)

I = log1 – log1/√2 

I = log\frac{1}{\frac{1}{\sqrt{2}}}

I = log√2  

Therefore, the value of \int_{\frac{\pi}{4}}^{\frac{\pi}{2}} cotxdx     is log√2.

Question 12. \int_{0}^{\frac{\pi}{4}} secxdx

Solution:

We have,

I = \int_{0}^{\frac{\pi}{4}} secxdx

I = \left[log(secx+tanx)\right]^{\frac{\pi}{4}}_0

I = log(secπ/4 + tanπ/4 – log(sec0 + tan0) 

I = log(√2 + 1) – log(1 + 0) 

I = log(\frac{\sqrt{2}+1}{1})

I = log(√2 + 1) 

Therefore, the value of \int_{0}^{\frac{\pi}{4}} secxdx     is log(√2 + 1).

Question 13. \int_{\frac{\pi}{6}}^{\frac{\pi}{4}} cosecxdx

Solution:

We have,

I = \int_{\frac{\pi}{6}}^{\frac{\pi}{4}} cosecxdx

I = \left[log|cosecx-cotx|\right]_{\frac{\pi}{6}}^{\frac{\pi}{4}}

I = [log|cosecπ/4 – cotπ/4|] – [log|cosecπ/6 – cotπ/6|]

I = [log|√2 – 1|] – [log|2 – √3|] 



I = log(\frac{\sqrt{2}-1}{2-\sqrt{3}})

Therefore, the value of \int_{\frac{\pi}{6}}^{\frac{\pi}{4}} cosecxdx     is log(\frac{\sqrt{2}-1}{2-\sqrt{3}})     .

Question 14. \int_{0}^{1} \frac{1-x}{1+x}dx

Solution: 

We have, 

I = \int_{0}^{1} \frac{1-x}{1+x}dx

Let x = cos 2t, so we have,

=> dx = –2 sin 2t dt

Now, the lower limit is,

=> x = 0

=> cos 2t = 0

=> 2t = π/2

=> t = π/4

Also, the upper limit is,

=> x = 1

=> cos 2t = 1

=> 2t = 0

=> t = 0

So, the equation becomes,

I = \int_{\frac{\pi}{4}}^{0} \frac{1-cos2t}{1+cos2t}(-2sin2t)dt

I = \int_{\frac{\pi}{4}}^{0}\frac{2sin^2t}{2cos^2t}(-2sin2t)dt

I = \int^{\frac{\pi}{4}}_{0}\frac{sin^2t}{cos^2t}(2sin2t)dt

I = \int^{\frac{\pi}{4}}_{0}\frac{sin^2t}{cos^2t}(4sintcost)dt

I = \int^{\frac{\pi}{4}}_{0}\frac{4sin^3t}{cost}dt

Let cos t = z, so we have,

=> – sin t dt = dz

=> sin t dt = – dz

Now, the lower limit is,

=> t = 0

=> z = cos t

=> z = cos 0



=> z = 1

Also, the upper limit is,

=> t = π/4

=> z = cos t

=> z = cos π/4

=> z = 1/√2

So, the equation becomes,

I = \int^{\frac{\pi}{4}}_{0}\frac{4sin^2t(sint)}{cost}dt

I = \int^{\frac{1}{\sqrt{2}}}_{1}\frac{-4(1-z^2)}{z}dz

I = -4\int^{\frac{1}{\sqrt{2}}}_{1}\frac{1-z^2}{z}dz

I = -4\int^{\frac{1}{\sqrt{2}}}_{1}(\frac{1}{z}-\frac{z^2}{z})dz

I = -4\int^{\frac{1}{\sqrt{2}}}_{1}(\frac{1}{z}-z)dz

I = -4\left[logz-\frac{z^2}{2}\right]^{\frac{1}{\sqrt{2}}}_1

I = -4[(log1/√2 – 1/2(2)) – (log1 – 1/2)]

I = -4[(log1/√2 – 1/4) – (0 – 1/2)]

I = -4[log1/√2 – 1/4 – 0 + 1/2]

I = -4[-log√2 + 1/4]

I = 4log√2 – 1 

I = 4 × 1/2log2 – 1

I = 2log2 – 1 

Therefore, the value of \int_{0}^{1} \frac{1-x}{1+x}dx     is 2log2 – 1.

Question 15. \int_{0}^{\pi} \frac{1}{1+sinx}dx

Solution: 

We have,

I = \int_{0}^{\pi} \frac{1}{1+sinx}dx

I = \int_{0}^{\pi} \frac{1-sinx}{(1+sinx)(1-sinx)}dx

I = \int_{0}^{\pi} \frac{1-sinx}{1-sin^2x}dx

I = \int_{0}^{\pi} \frac{1-sinx}{cos^2x}dx

I = \int_{0}^{\pi}\frac{1}{cos^2x}-\frac{sinx}{cos^2x}dx

I = \int_{0}^{\pi}sec^2x-\frac{sinx}{cosx(cosx)}dx

I = \int_{0}^{\pi}(sec^2x-tanxsecx)dx



I = \int_{0}^{\pi}sec^2xdx-\int_{0}^{\pi}tanxsecxdx

I = \left[tanx\right]^{\pi}_0-\left[secx\right]^{\pi}_0

I = [tan π – tan0] – [sec π – sec 0]

I = [0 – 0] – [–1 – 1]

I = 0 – (–2)

I = 2

Therefore, the value of \int_{0}^{\pi} \frac{1}{1+sinx}dx     is 2.

Question 16. \int_{\frac{-\pi}{4}}^{\frac{\pi}{4}} \frac{1}{1+sinx}dx

Solution: 

We have,

I = \int_{\frac{-\pi}{4}}^{\frac{\pi}{4}} \frac{1}{1+sinx}dx

I = \int_{\frac{-\pi}{4}}^{\frac{\pi}{4}} \frac{1-sinx}{(1+sinx)(1-sinx)}dx

I = \int_{\frac{-\pi}{4}}^{\frac{\pi}{4}} \frac{1-sinx}{1-sin^2x}dx

I = \int_{\frac{-\pi}{4}}^{\frac{\pi}{4}} \frac{1-sinx}{cos^2x}dx

I = \int_{\frac{-\pi}{4}}^{\frac{\pi}{4}}\frac{1}{cos^2x}-\frac{sinx}{cos^2x}dx

I = \int_{\frac{-\pi}{4}}^{\frac{\pi}{4}}sec^2x-\frac{sinx}{cosx(cosx)}dx

I = \int_{\frac{-\pi}{4}}^{\frac{-\pi}{4}}(sec^2x-tanxsecx)dx

I = \int_{\frac{-\pi}{4}}^{\frac{-\pi}{4}}sec^2xdx-\int_{\frac{-\pi}{4}}^{\frac{\pi}{4}}tanxsecxdx

I = \left[tanx\right]^{\frac{\pi}{4}}_{\frac{-\pi}{4}}-\left[secx\right]^{\frac{\pi}{4}}_{\frac{-\pi}{4}}

I = \left[tanx\right]^{\frac{\pi}{4}}_{\frac{-\pi}{4}}-\left[secx\right]^{\frac{\pi}{4}}_{\frac{-\pi}{4}}

I = [tan π/4 – tan(–π/4)] – [sec π/4 – sec (–π/4)]



I = [1 – (–1)] – [sec π/4 – sec (π/4)]

I = 2 – 0

I = 2

Therefore, the value of \int_{\frac{-\pi}{4}}^{\frac{\pi}{4}} \frac{1}{1+sinx}dx     is 2.

Question 17. \int_{0}^{\frac{\pi}{2}} cos^2xdx

Solution: 

We have,

I = \int_{0}^{\frac{\pi}{2}} cos^2xdx

I = \int_{0}^{\frac{\pi}{2}} (\frac{1+cos2x}{2})dx

I = \frac{1}{2}\int_{0}^{\frac{\pi}{2}} (1+cos2x)dx

I = \frac{1}{2}\int_{0}^{\frac{\pi}{2}}1dx+\frac{1}{2}\int_{0}^{\frac{\pi}{2}}cos2xdx

I = \frac{1}{2}\left[x\right]^{\frac{\pi}{2}}_0+\frac{1}{2}\left[\frac{sin2x}{2}\right]^{\frac{\pi}{2}}_0

I = \frac{1}{2}\left[x\right]^{\frac{\pi}{2}}_0+\frac{1}{4}\left[sin2x\right]^{\frac{\pi}{2}}_0

I = 1/2[π/2 – 0] + 1/4[sinπ – sin0]

I = 1/2[π/2] + 1/4[0 – 0]

I = π/4 

Therefore, the value of \int_{0}^{\frac{\pi}{2}} cos^2xdx      is π/4.

Question 18. \int_{0}^{\frac{\pi}{2}} cos^3xdx

Solution: 

We have,

I = \int_{0}^{\frac{\pi}{2}} cos^3xdx

I = \int_{0}^{\frac{\pi}{2}} \frac{cos3x+3cosx}{4}dx



I = \frac{1}{4}\int_{0}^{\frac{\pi}{2}} (cos3x+3cosx)dx

I = \frac{1}{4}\int_{0}^{\frac{\pi}{2}} cos3xdx+\frac{3}{4}\int_{0}^{\frac{\pi}{2}}cosxdx

I = \frac{1}{4}\left[\frac{sin3x}{3}\right]^{\frac{\pi}{2}}_0+\frac{3}{4}[sinx]^{\frac{\pi}{2}}_{0}

I = \frac{1}{12}\left[sin3x\right]^{\frac{\pi}{2}}_0+\frac{3}{4}[sinx]^{\frac{\pi}{2}}_{0}

I = 1/12 [-1 – 0] + 3/4[1 – 0]

I = 3/4 – 1/12

I = (9 – 1)/12

I = 8/12

I = 2/3

Therefore, the value of \int_{0}^{\frac{\pi}{2}} cos^3xdx      is 2/3.

Question 19. \int_{0}^{\frac{\pi}{6}} cosxcos2xdx

Solution: 

We have,

I = \int_{0}^{\frac{\pi}{6}} cosxcos2xdx

I = \frac{1}{2}\int_{0}^{\frac{\pi}{6}} 2cosxcos2xdx

I = \frac{1}{2}\int_{0}^{\frac{\pi}{6}} (cos3x + cosx)dx

I = \frac{1}{2}\int_{0}^{\frac{\pi}{6}}cos3xdx + \frac{1}{2}\int_{0}^{\frac{\pi}{6}}cosxdx

I = \frac{1}{2}\left[\frac{sin3x}{3}\right]^{\frac{\pi}{6}}_0 + \frac{1}{2}\left[sinx\right]^{\frac{\pi}{6}}_0

I = \frac{1}{6}\left[sin3x\right]^{\frac{\pi}{6}}_0 + \frac{1}{2}\left[sinx\right]^{\frac{\pi}{6}}_0

I = 1/6[sinπ/2 – sin0] + 1/2[sinπ/6 – sin0]

I = 1/6[1 – 0] + 1/2[1/2 – 0]



I = 1/6 + 1/4

I = (4 + 6)/24 

I = 10/24 

I = 5/12 

Therefore, the value of \int_{0}^{\frac{\pi}{6}} cosxcos2xdx      is 5/12.

Question 20. \int_{0}^{\frac{\pi}{2}} sinxsin2xdx

Solution: 

We have,

I = \int_{0}^{\frac{\pi}{2}} sinxsin2xdx

I = \frac{1}{2}\int_{0}^{\frac{\pi}{2}} 2sinxsin2xdx

I = \frac{1}{2}\int_{0}^{\frac{\pi}{2}} (cosx - cos3x)dx

I = \frac{1}{2}\int_{0}^{\frac{\pi}{2}}cosxdx - \frac{1}{2}\int_{0}^{\frac{\pi}{2}}cos3xdx

I = \frac{1}{2}\left[sinx\right]^{\frac{\pi}{2}}_0-\frac{1}{2}\left[\frac{sin3x}{3}\right]^{\frac{\pi}{2}}_0

I = \frac{1}{2}\left[sinx\right]^{\frac{\pi}{2}}_0-\frac{1}{6}[sin3x]^{\frac{\pi}{2}}_0

I = 1/2[sinπ/2 – sin0] – 1/6[sin3π/2 – sin0]

I = 1/2[1 – 0] – 1/6[-1 – 0]

I = 1/2 – 1/6(-1)

I = 1/2 + 1/6 

I = (6 + 2)/12

I = 8/12 

I = 2/3

Therefore, the value of \int_{0}^{\frac{\pi}{2}} sinxsin2xdx      is 2/3.

Question 21. \int_{\frac{\pi}{3}}^{\frac{\pi}{4}} (tanx+cotx)^2dx

Solution: 

We have,

I = \int_{\frac{\pi}{3}}^{\frac{\pi}{4}} (tanx+cotx)^2dx

I = \int_{\frac{\pi}{3}}^{\frac{\pi}{4}} (\frac{sinx}{cosx}+\frac{cosx}{sinx})^2dx

I = \int_{\frac{\pi}{3}}^{\frac{\pi}{4}} (\frac{sin^2x+cos^2x}{cosxsinx})^2dx

I = \int_{\frac{\pi}{3}}^{\frac{\pi}{4}} (\frac{1}{cosxsinx})^2dx

I = \int_{\frac{\pi}{3}}^{\frac{\pi}{4}}\frac{1}{cos^2xsin^2x}dx

I = \int_{\frac{\pi}{3}}^{\frac{\pi}{4}}\frac{4}{4cos^2xsin^2x}dx

I = \int_{\frac{\pi}{3}}^{\frac{\pi}{4}}\frac{4}{(sin2x)^2}dx



I = 4\int_{\frac{\pi}{3}}^{\frac{\pi}{4}}cosec^22xdx

I = 4\left[\frac{-cot2x}{2}\right]_{\frac{\pi}{3}}^{\frac{\pi}{4}}

I = 2\left[-cot2x\right]_{\frac{\pi}{3}}^{\frac{\pi}{4}}

I = 2[-cotπ/2 + cot2π/3]

I = 2[-1/√3 – 0]

I = -2/√3 

Therefore, the value of \int_{\frac{\pi}{3}}^{\frac{\pi}{4}} (tanx+cotx)^2dx      is -2/√3.

Question 22. \int_{0}^{\frac{\pi}{2}} cos^4xdx

Solution: 

We have,

I = \int_{0}^{\frac{\pi}{2}} cos^4xdx

I = \int_{0}^{\frac{\pi}{2}} (cos^2x)^2dx

I = \int_{0}^{\frac{\pi}{2}} (\frac{1+cos2x}{2})^2dx

I = \frac{1}{4}\int_{0}^{\frac{\pi}{2}} (1+cos2x)^2dx

I = \frac{1}{4}\int_{0}^{\frac{\pi}{2}} (1+cos^22x+2cos2x)dx

I = \frac{1}{4}\int_{0}^{\frac{\pi}{2}} (1+\frac{1+cos4x}{2}+2cos2x)dx

I = \frac{1}{4}\left[x+\frac{x}{2}+\frac{sin4x}{8}+sin2x\right]^{\frac{\pi}{2}}_0

I = 1/4[π/2 + π/4 + 0 + 0 – 0 – 0 – 0 – 0]

I = 1/4[3π/4] 

I = 3π/16 

Therefore, the value of \int_{0}^{\frac{\pi}{2}} cos^4xdx     is 3π/16.

Attention reader! All those who say programming isn’t for kids, just haven’t met the right mentors yet. Join the  Demo Class for First Step to Coding Coursespecifically designed for students of class 8 to 12. 

The students will get to learn more about the world of programming in these free classes which will definitely help them in making a wise career choice in the future.




My Personal Notes arrow_drop_up
Recommended Articles
Page :